Functionalization of graphene oxide with naphthalenediimide diamine for high-performance cathode materials of lithium-ion batteries. Issue 4 (30th January 2018) - Song, Yidan; Gao, Yuanrui; Rong, Hongren; Wen, Hao; Sha, Yanyong; Zhang, Hanping; Liu, Hong-Jiang; Liu, Qi
Abstract : Naphthalenediimide diamine-functionalized graphene oxide exhibited a high specific capacity and good cyclic stability as a cathode material of lithium batteries. Abstract : Through the covalent bonding between naphthalenediimide diamine (NDIDA) and graphene oxide (GO), we synthesize NDIDA-functionalized graphene oxide (NDIDA-GO). The as-synthesized NDIDA-GO is characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, thermogravimetric analysis, Raman spectroscopy, X-ray photoelectron spectroscopy, scanning electron microscopy, transmission electron microscopy, and the Brunauer–Emmett–Teller surface area analysis. As a cathode material for lithium-ion batteries, within a voltage window of 4.5–1.5 V, NDIDA-GO exhibits a high specific capacity, good cyclic stability, and rate capability, keeping a specific capacity of 240 mA h g −1 after 50 cycles at 50 mA g −1 . This work provides an effective route for the development of high-performance organic-based cathode materials for lithium-ion batteries.